Pengaruh Reputasi Underwriter, Reputasi Auditor Dan Financial Leverage Terhadap Underpricing Saham IPO dI BEI - Febrian, Adelina Everesta; Mulyani, Erly (Universitas Negeri Padang, 2026)
This research was conducted with the aim of 1) Is there an influence of Underwriter Reputation on Underpricing of IPO shares. 2) Is there an influence of Auditor Reputation on Underpricing of IPO shares. 3) Is there an influence of financial leverage on underpricing of IPO shares. This research uses quantitative data with source data from the company's prospectus and financial reports. The sample for this research is 158 companies that conducted an IPO from 2019-2023. The analytical method used in this research is descriptive analysis,normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple regression analysis, determinant coefficient test, simultaneous test (F) and partial test (T). The results of this research are that underwriter reputation, auditor reputation and financial leverage have no effect on underpricing of shares on the IDX